Anti-Cancer Effects of Panax ginseng Berry Polysaccharides via Activation of Immune-Related Cells - Lee, Dae-Young; Park, Chan Woong; Lee, Sue Jung; Park, Hye-Ryung; Kim, Su Hwan; Son, Seung-U; Park, Jiyong; Shin, Kwang-Soon (Frontiers in Pharmacology, 2019)
Panax ginseng has long been used as natural medicine and health food all over the world. Cancer is a major cause of death worldwide and its prognosis likely depends on the immune system during tumor treatment. In this study, ginseng berry polysaccharides were evaluated for their immunostimulant and anti-cancer effects. Ginseng berry polysaccharide portion (GBPP) was used to investigate its effects on anti-complementary activity, peritoneal macrophage activation, and natural killer (NK) cell cytotoxicity. Moreover, both i.v. and p.o administration of GBPP prior to B16-BL6 melanoma implantation in mice was evaluated. GBPP significantly increased the anti-complementary activity and cytokine production including interleukin (IL)-6, IL-12, and tumor necrosis factor (TNF)-α, dose-dependently. Splenocytes obtained after i.v. administration of GBPP showed cytolytic activity in Yac-1 cells in proportion to the E/T ratio. In addition, GBPP enhanced the production of interferon (IFN)-γ and granzyme B of NK cells. For the experimental lung cancer, compared with control mice, GBPP delivered by i.v. suppressed cancer by 48% at 100 μg/mouse, while a 37% reduction was achieved by oral administration. Deficient of NK cells in animal model demonstrated that the anti-cancer effect of GBPP was through NK cell activation. Results of this study suggest that ginseng berry polysaccharides, owing to their modulation of the immune response, can be a potential curative applicant for the prevention and treatment of tumors.